Plan de negocios para la creación de una empresa e - commerce de frutas y verduras orgánicas, en la ciudad de Tunja - Boyacá (2021)
This document shows a market, technical, operational, financial study following the requirements for the implementation of the business plan ¨Organic Food¨ aimed at the marketing and distribution of organic fruits and vegetables online, in the city of Tunja .